Antimicrobial and Antibiofilm Activities of New Synthesized Silver Ultra-NanoClusters (SUNCs) Against Helicobacter pylori - Grande, Rossella; Sisto, Francesca; Puca, Valentina; Carradori, Simone; Ronci, Maurizio; Aceto, Antonio; Muraro, Raffaella; Mincione, Gabriella; Scotti, Luca (Frontiers in Microbiology, 2020)
Helicobacter pylori colonizes approximately 50% of the world’s population and it is the cause of chronic gastritis, peptic ulcer disease and gastric cancer. The increase of antibiotic resistance is one of the biggest challenges of our century due to its constant increase. In order to identify an alternative or adjuvant strategy to the standard antibiotic therapy, the in vitro activity of newly synthesized Silver Ultra-NanoClusters (SUNCs), characterized by an average size inferior to 5 nm, against clinical strains of Helicobacter pylori, with different antibiotic susceptibilities, was evaluated in this study. MICs and MBCs were determined by the broth microdilution method, whereas the effect of drug combinations by the checkerboard assay. The Minimum Biofilm Eradication Concentration (MBEC) was measured using AlamarBlue (AB) assay and Colony Forming Unit (CFU) counts. The cytotoxicity was evaluated by performing the MTT assay on AGS cell line. The inhibitory activity was expressed in terms of bacteriostatic and bactericidal potential, with MIC50, MIC90, and MBC50 of 0.33 mg/L against planktonic Helicobacter pylori strains. Using the fractional inhibitory concentration index, SUNCs showed synergism with metronidazole in one clinical strain, and very close to synergistic effect on the reference strain; the combination with clarythromicin evidenced an effect very close to synergism on both strains considered. The biofilm eradication was obtained after treatment with 2X, 3X and 4X MIC value. Moreover, SUNCs showed low toxicity on human cells and was effective in eradicating a mature biofilm produced by H. pylori. The data presented in this study demonstrate that SUNCs could represent a novel strategy for the treatment of H. pylori infections either alone or in combination with metronidazole.